Estimation of Antioxidant Levels in Saliva and Serum of Chronic Periodontitis Patients with and without Ischemic Heart Disease - Anahita Punj; Santhosh Shenoy; N. Suchetha Kumari; Priyanka Pampani (International Journal of Dentistry)
Objective. To investigate whether there is a relationship between periodontitis and ischemic heart disease by estimation of total antioxidant status in saliva and serum. Materials and Methods. A total of 80 samples were collected and divided equally into 4 groups of healthy controls, chronic periodontitis patients, ischemic heart disease patients with periodontitis, and ischemic heart disease patients without periodontitis. Saliva and venous blood samples were collected and analyzed for levels of total antioxidant capacity, superoxide dismutase, glutathione peroxidase, and catalase. Results. There were significant (p<0.05) differences in the mean serum levels of total antioxidant capacity (p<0.001), superoxide dismutase (p<0.001), glutathione peroxidase (p<0.006), and catalase (p<0.001) within the 4 groups, whereas the mean salivary levels were significant only for glutathione peroxidase (p=0.001). Both of these serum and salivary antioxidant levels were lower in disease groups of IHD + CP, IHD + H, and CP as compared to healthy controls, with different patterns. Conclusion. Antioxidant capacity is significantly hampered in chronic periodontitis and ischemic heart disease patients with or without periodontitis as compared to healthy controls. The salivary and serum antioxidants may not follow the same increase or decrease as a result of increased oxidant stress due to disease.